Male Victims of Family Physical Violence and Associated Forensic Aspects - kasemtavornsin, puimek (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aimed to study the characteristics of violence against men aged 18 and over who were physically assaulted by family members and issues related to forensic aspects. Methods A retrospective analytic study of 225 male patients aged 18 or over who had been physically abused by family members and had received treatment or were autopsied at the forensic department of Nakornping Hospital during the six-year period from June 2018 through May 2024. Results Of the 225 individuals included in the study, 218 had been injured and 7 had died of their injuries. The highest incidence occurred in the 30-39 age group. The plurality of perpetrators of physical violence, a total of 65 individuals, was intimate partners, (28.89%). Weapons or other objects were used in 164 cases (72.89%), with knives being the most common, used in 92 cases (40.89%). The most frequently damaged parts of the body were the head, face, and arms, affected in 147 cases (65.33%). Most victims sustained injuries to multiple parts of the body. A total of 180 injured individuals (80.00%) were hospitalized. Only 65 victims (28.89%) reported the incidents to the police. Most of the victims of violence by relatives were either age 30-39 or over 60. The majority of the perpetrators were men, and the violence typically resulted in injuries to the upper part of the body. Conclusions Male victims of family physical violence account for one-third of all domestic assaults. Individuals in their 30s are the most often abused. Injuries tended to be quite severe, often requiring hospitalization. This violence strains the healthcare system, the justice process budget and results in a loss of labor in the economy. Appropriate guidelines for assisting patients who are victims of domestic violence should ensure that treatment is provided without discrimination and with equality of human rights for both men and women.